Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/0885066615601046
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Respiratory Failure in Patients With Hematological Malignancy

Abstract: Acute respiratory failure (ARF) is the leading cause of ICU admission in patients with hematologic malignancies and is associated with a high mortality. The main causes of ARF are bacterial and opportunistic pulmonary infections and noninfectious lung disorders. Management consists of a systematic clinical evaluation aimed at identifying the most likely cause, which in turn, determines the best first-line empirical treatments. The need for mechanical ventilation is a major determinant of prognosis. Several stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 92 publications
0
10
0
1
Order By: Relevance
“…Exclusion criteria for the study were < 18 years of age, need for ECMO as bridge, or intraoperative during lung transplant or other surgical procedures, and veno-arterial configuration (combined respiratory/cardiac disease). 19…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria for the study were < 18 years of age, need for ECMO as bridge, or intraoperative during lung transplant or other surgical procedures, and veno-arterial configuration (combined respiratory/cardiac disease). 19…”
Section: Methodsmentioning
confidence: 99%
“…Patients with ARDS on mechanical ventilation during an ICU admission have a mortality rate exceeding 75%. 11 Our patient suddenly developed ARDS in the setting of a newly diagnosed AML, underwent IC while on VV-ECMO due to a lack of improvement to conventional mechanical ventilation and other supportive strategies. Since the late 1970s, ECMO has been used in patients with acute respiratory failure to improve survival outcomes, but early studies demonstrated no therapeutic benefit.…”
Section: Discussionmentioning
confidence: 90%
“…10 Acute respiratory failure is the leading cause of ICU admissions in this patient population and accounts for 10-20% of ICU admissions in those with acute leukemia and approximately 50% for those with neutropenia. 11 Both subsets of patients have a high morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…В зарубежной литературе упоминается как минимум о 175 пациентах со злокачественными новообразованиями крови, которым с целью купирования дыхательной недостаточности, развившейся вследствие специфического или неспецифического поражения легких, применяли ЭКМО [22][23][24]. Выживаемость пациентов этой группы в различных исследованиях варьировала от 0-50% [23][24][25][26].…”
Section: Introductionunclassified